2021
DOI: 10.3390/microorganisms9102009
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Valent Iron Filtration Reduces Microbial Contaminants in Irrigation Water and Transfer to Raw Agricultural Commodities

Abstract: Groundwater depletion is a critical agricultural irrigation issue, which can be mitigated by supplementation with water of higher microbiological risk, including surface and reclaimed waters, to support irrigation needs in the United States. Zero-valent iron (ZVI) filtration may be an affordable and effective treatment for reducing pathogen contamination during crop irrigation. This study was performed to determine the effects of ZVI filtration on the removal and persistence of Escherichia coli, and pepper mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Rifampicin in LPBR may create a low selection pressure to those cells that may have lost their rifampicin resistance, but this potential limiting factor occurs in all traditional MPN methods that utilize TSBR followed by plate confirmation. In addition, inclusion of rifampicin in TSB for MPN assays has been widely accepted in agricultural research (Anderson‐Coughlin et al, 2021; Limoges et al, 2022; Moyne et al, 2022; Weller, Kovac, Kent, et al, 2017; Weller, Kovac, Roof, et al, 2017), and the results in the current study revealed no statistical significance between the broths with and without the inclusion of rifampicin. Therefore, the LPBR MPN assays verified in this study generated comparable results as of the traditional MPN methods using TSB or TSBR followed by MACR plating.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Rifampicin in LPBR may create a low selection pressure to those cells that may have lost their rifampicin resistance, but this potential limiting factor occurs in all traditional MPN methods that utilize TSBR followed by plate confirmation. In addition, inclusion of rifampicin in TSB for MPN assays has been widely accepted in agricultural research (Anderson‐Coughlin et al, 2021; Limoges et al, 2022; Moyne et al, 2022; Weller, Kovac, Kent, et al, 2017; Weller, Kovac, Roof, et al, 2017), and the results in the current study revealed no statistical significance between the broths with and without the inclusion of rifampicin. Therefore, the LPBR MPN assays verified in this study generated comparable results as of the traditional MPN methods using TSB or TSBR followed by MACR plating.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, scientists routinely use a generic surrogate adapted for specific antibiotic resistance to facilitate selective plate enumeration. For example, E. coli TVS353 with rifampicin resistance has been widely used in agricultural studies in the United States (Anderson‐Coughlin et al, 2021; Limoges et al, 2022; Moyne et al, 2022; Sharma et al, 2016; Sharma et al, 2019; Weller et al, 2019; Weller, Kovac, Kent, et al, 2017; Weller, Kovac, Roof, et al, 2017; Wright et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their promise, Fe 0 filters have so far failed to attain the expected widespread adoption within low-income communities [29,[143][144][145][146][147]. To be commercially viable, the costs of producing, marketing, and distributing Fe 0 filters should be covered by the purchase price paid for the product by the consumer.…”
Section: Economics Of Fe 0 Filtersmentioning
confidence: 99%